The complete mitochondrial genome of the bass yabby Trypaea australiensis Dana 1852, (Crustacea; Decapoda; Callianassidae) – a new gene order for the Decapoda. (1st November 2016) - Gan, Huan You; Gan, Han Ming; Lee, Yin Peng; Austin, Christopher M.
Abstract: The complete mitochondrial genome of the Bass yabby Trypaea australiensis was obtained from a partial genome scan using the MiSeq sequencing system. The T. australiensis mitogenome is 16, 821 bp in length (70.25% A + T content) made up of 13 protein-coding genes, 2 ribosomal subunit genes, 22 transfer RNAs and a putative 1977 bp non-coding AT-rich region. This Trypaea mitogenome sequence is the 5th for the family Callianassidae and represents a new gene order for the Decapoda involving protein-coding, rRNA and tRNA genes and the control region.